2013
DOI: 10.1038/labinvest.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes in renal genes dysregulated in mouse and rat models of type 1 diabetes

Abstract: Epigenetic processes are increasingly being recognized as factors in the pathophysiology of diabetes complications, but few chromatin studies have been done in diabetic nephropathy (DN). We hypothesized that changes in mRNA expression of DN-related genes are associated with epigenetic alterations and aberrant expression of histone-modifying enzymes. RT-PCR and a matrix-chromatin immunoprecipitation platform were used to examine renal mRNA expression, RNA polymerase II (Pol II) recruitment, and epigenetic marks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…A previous report showed that upregulation of CCL2, linked to hypermethylation of H3K4 and hypomethylation of H3K27, is associated with kidney damage in diabetes (108). In addition, we recently demonstrated that CCL2 expression is upregulated in macrophages after peripheral nerve injury in a model of neuropathic pain, and is linked to a shift toward euchromatin, based on H3K4me 3 and H3K9Ac modifications (109) (Figure 1).…”
Section: Histone Methylation and Ccl2mentioning
confidence: 64%
“…A previous report showed that upregulation of CCL2, linked to hypermethylation of H3K4 and hypomethylation of H3K27, is associated with kidney damage in diabetes (108). In addition, we recently demonstrated that CCL2 expression is upregulated in macrophages after peripheral nerve injury in a model of neuropathic pain, and is linked to a shift toward euchromatin, based on H3K4me 3 and H3K9Ac modifications (109) (Figure 1).…”
Section: Histone Methylation and Ccl2mentioning
confidence: 64%
“…In an in vivo study [67], increases in RNA polymerase II recruitment and H3K4me2, but decreases in H3K27me3 levels, were associated with the expression of diabetic nephropathy-related genes in mouse and rat models of diabetic nephropathy, with some differences between the two species. In other studies, high glucose increased the expression of the redox-regulating protein p66Shc by inhibiting promoter DNAme and increasing H3K9ac in podocytes in vitro and in experimental diabetic nephropathy [68].…”
Section: Introductionmentioning
confidence: 99%
“…Aldosterone plays a significant role in the development of CKD and evidence suggests that FKBP51 protein and mRNA expression are induced by aldosterone in the kidney and intestinal tissues [108][109][110] . On the other hand, CypA has a role in renal acidosis 111 , diabetic nephropathy 112 and renal cell carcinoma 113 . Furthermore, Pin1 inhibition affects CKD associated with secondary parathyroidism 114 .…”
Section: The Role Of Ppiases In Ckdmentioning
confidence: 99%